2008
DOI: 10.1139/p07-155
|View full text |Cite
|
Sign up to set email alerts
|

Study of the frequency fluctuations of a semiconductor diode laser

Abstract: Frequency fluctuations of an inexpensive single-mode semiconductor diode laser, which operates in the 822 nm region, are investigated by direct measurement of the error signal. The linear slope of first derivative signal of a transition in the (2,1,1) vibration-rotation band of water vapour is used as a frequency discriminator. A balanced photodetector is used to reduce the intensity noise and to improve the S/N ratio. Frequency stability of the diode laser is investigated when the laser is under a free-runnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…After closing the PI loop, the error signal is recorded for each of the discriminator. The recorded error signal is FFT analysed and the resultant data is used for the calculation of square root of Allan variance σ (2, τ ) using the equation [26][27][28]:…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After closing the PI loop, the error signal is recorded for each of the discriminator. The recorded error signal is FFT analysed and the resultant data is used for the calculation of square root of Allan variance σ (2, τ ) using the equation [26][27][28]:…”
Section: Resultsmentioning
confidence: 99%
“…It is observed that at τ = 10 s, the EIT (TPA) locked probe laser attains a stability of σ ∼ 1.2 × 10 −12 (2.35 × 10 −12 ) whereas the pump laser shows σ ∼ 2.4 × 10 −12 . The above-mentioned method of measuring frequency stability under closed-loop condition does not consider the noise of the discriminator [28] because the error signal is weighted by the servo loop transfer function H ( f ). In effect, the values of σ (2, τ ) calculated earlier predicts the best case of frequency stability [28].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The noise power of the pump laser is more than that of the probe within f = 100 HZ → 1 kHz, while the probe laser noise is more within f = 100 mHz → 30 Hz. The Allan variance σ 2 (2, τ ) is calculated from S ν ( f ) using the relation [13,14,28,29]…”
Section: Atomic Frequency Offset Locking With Aulter-townes Signalmentioning
confidence: 99%